A comparative study of the expectations of SME employers recruiting young people in Germany, Australia and the United States - Zenner-Höffkes, Lea [Verfasser]; Harris, Roger [Verfasser]; Zirkle, Chris [Verfasser]; Pilz, Matthias [Verfasser] (My University, 2021)
„Debate continues to feature prominently in many countries on such notions as skills, skill shortages and employability. Clearly such notions remain significant internationally in the rhetoric of both economic reform and training policy and practice. However, the problem remains of differing perceptions. The purpose of this comparative study was to examine the expectations of small and medium-sized enterprises (SMEs) when they recruit young people. Focusing on Germany, Australia and the United States, interviews were held with 30 managers in two diverse job roles—hospitality front-desk staff and automotive technicians. In addition to differences in the range of desired skills between the job roles in these countries, difficulties in recruiting young people were highlighted by the study. Generational differences and academization were perceived as having effects on the hiring of young workers. Various problems with each country's general education system were also emphasized, as managers perceived many young people being inadequately prepared for work. The study also demonstrates the influence of the skill formation system of the countries is less relevant in comparison to the sector in which the SMEs are active.“ (authors’ abstract; BIBB-Doku)
Keywords: S 3.2.1 KMU, Klein- und Mittlere Unternehmen; G 1.3.2.2 Übergänge; I 2.3.2 Nordamerika; I 2.3.5 Australien, Ozeanien; I 2.1 Deutschland; 370; Klein- und Mittelbetrieb; Ausbildungsbetrieb; Ausbildungsverhalten; Personalgewinnung; Erwartung; Ausbildungseignung; Beschäftigungsfähigkeit; USA; Australien; Bundesrepublik Deutschland; Internationaler Vergleich